Cultural Contexts of the Lifelong Learning Concept - Malewski, Mieczysław (INSTED: Interdisciplinary Studies in Education & Society, 2016)
In the article the author analyses economic, social and cultural conditions, which contributed to the idea of lifelong learning in adults and its impact on the sphere of professional education and work. The author believes that sudden changes in the economy and turbulences on the employment market force us to consider whether the traditional model of professional education, where education precedes taking on a job, is still to be maintained. Perhaps the so-far relation ?first education and then work? should be replaced by the solution of ?first work and then education?. The observed dynamics of post-modernism provides arguments for such a change.